Restricted Nitrate Influx and Reduction in Corn Seedlings Exposed to Ammonium - MacKown, Charles T. (1982)
The effect of ambient ammonium (0.5 millimolar [(14)NH(4)](2)SO(4)) added to a nutrient solution containing 1.0 millimolar K(15)NO(3), 99 atom per cent (15)N, upon [(15)N]nitrate assimilation and utilization of previously accumulated [(14)N]nitrate was investigated. Corn seedlings, 5-day-old dark-grown decapitated (experiment I) and 10-day-old light-grown intact (experiment II), which had previously been grown on K(14)NO(3) nutrient solution, were used. In both experiments, the presence of ambient ammonium decreased [(15)N]nitrate influx (20% after 6 hours) without significantly affecting the efflux of previously accumulated [(14)N]nitrate. In experiment I, relative reduction of [(15)N]nitrate (reduction as a percentage of influx) was inhibited more than was [(15)N]nitrate influx. Nevertheless, in experiment I, where all reduction could be assigned to the root system, the absolute inhibition of reduction during the 12 hours (13 micromoles/root) was less than the absolute inhibition in influx (24 micromoles/root). The data suggest that the influence of ammonium on [(15)N]nitrate influx could not be totally accounted for by the decrease in the potential driving force which resulted from restricted reduction; an additional impact on the influx process is indicated. Reduction of [(15)N]nitrate in experiment II after 6 hours accounted for 30 and 18% of the tissue excess (15)N in the control and ammonium treatments, respectively. Relative distribution of (15)N between roots and exudate (experiment I), or between roots and shoots (experiment II) was not affected by ammonium. On the other hand, the accumulation of [(15)N]nitrate in roots, shoots, and xylem exudate was enhanced by ammonium treatment compared to the control, whereas the accumulation of reduced (15)N was inhibited.